Effect of roscovitine and cycloheximide on ultrastructure of sheep oocytes - Crocomo, Letícia Ferrari [UNESP]; Filho, Wolff Camargo Marques [UNESP]; Sudano, Mateus José [UNESP]; Paschoal, Daniela Martins [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP]; Bicudo, Sony Dimas [UNESP] (Elsevier, 2013)
It is believed the temporary meiosis arrest with roscovitine or cycloheximide may improve the in vitro developmental competence of oocytes in different animal species. However, little is known about the effects of these inhibitors on ultrastructure of ovines cumulus-oocyte complexes (COCs). The aim of this study was to evaluate the progression of cytoplasmic maturation and the ultrastructural changes in sheep COCs exposed to roscovitine or cycloheximide, at acceptable concentrations. COCs were in vitro cultured for 24. h in maturation medium (control group) containing 100 μM roscovitine or 1 μg/mL cycloheximide (treatment groups). After this time, some COCs were cultured for further 22. h in inhibitor-free medium. The ultrastructure organization of COCs was evaluated by transmission electron microscopy before (immature group) and after in vitro culture for 24 and 46. h. As expected, signs of immaturity and maturity were observed in immature and control groups, respectively. In treatment with roscovitine, there were cumulus cells degeneration, swelling of mitochondrias, few cortical granules and many vesicles with electron-dense material. However, in cycloheximide treatment there were not signs of degeneration or cellular senescence. Metabolic units and mitochondrial pleomorphism were found in all experimental groups. These evidences demonstrate that roscovitine promoted irreversible ultrastructural changes while cycloheximide did not affect the cytoplasmic maturation. However, the implications on embryo development are still unclear. © 2012 Elsevier B.V.
Keywords: Cytoplasmic maturation; Meiosis inhibitors; Oocyte; Ovine; Animalia; Ovis; Ovis aries